RECOVERY GARAM LITHIUM DARI AIR ASIN (BRINE) DENGAN METODA PRESIPITASI - Sumarno Sumarno; Ratnawati Ratnawati; A. Nugroho A. Nugroho (TEKNIK, 2012)
Lithium demand increases as it is widely used as raw material for rechargeable battery, alloy for airplane, andfuel for fusion nuclear reactor. Lithium is an extremely reactive element, that it is never found as free element innature. Lithium compounds are found in earth crust, with very small concentration (20 – 70 ppm) and totalcontent of more than 20 million tons. The biggest lithium reserve is in seawater (0,14 – 0,25 ppm) andgeothermal water (7 ppm) with total amount of 230 billion tons. There is no industry applies the technology torecover lithium from seawater. Having a vast sea area and abundant geothermal sources, Indonesia needs todevelop a technology to recover lithium from both sources. This research is aimed to recover lithium fromgeothermal water. The experiment was conducted using synthetic and geothermal water with lithiumconcentration range of 220 – 400 ppm, temperature range of 20 – 40°C, and mixing time range of 1 – 4 hours.The experiment was designed with 2 level factorial design. The results show that the most influencing variable ismixing time, while significant interaction amongst variables is not observed. Further experiment usinggeothermal water from Bledug Kuwu with initial lithium concentration of 400 ppm and temperature 30°Cresulted in optimum mixing time, i.e. 3 hours with 92,5% of the lithium could be recovered